Impacto da Crescente Penetração de Produção Renovável no Mercado Ibérico de Eletricidade (MIBEL) a longo prazo - João Pedro Gomes Vaz Pinto (2020)
Electric power production in the Iberian Peninsula has been undergoing several changes in recent decades. These changes are based on the increasing production from renewable sources and the growing concern about environmental issues, framed within a strategy of transition to a carbon-neutral economy. With this change, significant impacts are expected on the profile of hourly prices in a liberalised market regime, namely on the Spot (OMIE) and Futures (OMIP) market prices. This work aims to understand the impacts of the integration of renewable energies on the prices of these markets, based on the theoretical assumptions of the energy markets and the targets proposed by the governments, for the continuous investment in renewable energies. Assuming that renewable technologies have lower marginal production costs than other producing technologies in the energy market, the resulting market prices are expected to decrease as renewable production increases. Therefore, a simulation of different integration scenarios of renewable production and the analysis of the impacts on prices at MIBEL are carried out. For this purpose, the scenarios were created, where renewable production was increased to the values that are expected to be reached in 2030, allowing the creation of models of price forecasting. The forecasting models are developed through Artificial Neural Networks (ANN), implemented through the Matlab NFTOOL tool. These models allow an analyst to obtain the price values for the period under analysis with the increase in renewable production, and compare them with the price values for the same period, with the real production values, to perceive the influence of the renewable production increase, in the price of electricity.